QUALITY OF CRITICAL THINKING, COMMUNICATION, COLLABORATION AND CREATIVITY SKILLS: SURVEY OF HIGH SCHOOL STUDENTS IN BIOLOGY LEARNING - Sari, Tasya Novian Indah; Rakhmawati, Anna; Ratnawati, Dwi; Purwanti, Nunuk; Yulianti, Yulianti (Didaktika Biologi: Jurnal Penelitian Pendidikan Biologi, 2025)
Students need critical thinking, creativity, communication and collaboration skills to face and adapt to social change, so that students can survive and compete well in social life. The aim of the research is to describe the critical thinking, collaboration, communication and creativity skills of high school students in biology learning. The research was carried out in August-September 2023. The research population was high school students in Magetan Regency. The research sampling technique was cluster sampling and the research sample was 539 high school class students. Data collection techniques used questionnaires on critical thinking skills, communication, collaboration and creativity. This research instrument is a questionnaire in the form of a questionnaire with 5 Likert scales. Quantitative descriptive research data analysis techniques. The research results show that high school students' critical thinking and creativity skills are in the medium and low categories compared to communication and collaboration skills. The results of the research can be used as a reflection for teachers or future researchers as a follow-up to empower students' critical thinking, communication, collaboration and creativity skills in implementing the Merdeka Curriculum.